Comparison of serum creatinine levels in different color/race categories in a Brazilian population - Roberto Carlos de Brito Barcellos; Jorge Paulo Strogoff de Matos; Hye Chung Kang; Maria Luiza Garcia Rosa; Jocemir Ronaldo Lugon (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2015)
Serum creatinine (sCr) is usually higher among black people in the United States due to increased muscle mass, justifying the addition of race adjustment in creatinine-based formulas to estimate glomerular filtration rate (eGFR). We aimed to assess if sCr levels are different in low-income communities in Brazil according to their race. A total of 1,303 participants were enrolled (58% females, 50±14 years-old, 33% self-defined as white, 41% as mixed race, and 26% as black). No significant differences in sCr were found between racial groups and no influence of race on sCr was seen in the linear regression analysis. The eGFR, calculated using the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) formula with no race adjustment, was no different between whites, mixed race and blacks. However, using such adjustment, eGFR for mixed race and black individuals was significantly higher than for whites (p < 0.001). In conclusion, no significant differences in sCr levels were found between racial groups, raising doubts as to whether race adjustment in eGFR formula should be used in that population.